2012
DOI: 10.1002/asia.201100826
|View full text |Cite
|
Sign up to set email alerts
|

Group 3 Metal Initiators with an [OSSO]‐Type Bis(phenolate) Ligand for the Stereoselective Polymerization of Lactide Monomers

Abstract: A series of 1,ω-dithiaalkanediyl-bridged bis(phenols) of the general type [OSSO]H(2) with variable steric properties and various bridges were prepared. The stoichiometric reaction of the bis(phenols) 1,3-dithiapropanediyl-2,2'-bis(4,6-di-tert-butylphenol), 1,3-dithiapropanediyl-2,2'-bis[4,6-di(2-phenyl-2-propyl)phenol], rac-2,3-trans-propanediyl-1,4-dithiabutanediyl-2,2'-bis[4,6-di(2-phenyl-2-propyl)phenol], rac-2,3-trans-butanediyl-1,4-dithiabutane diyl-2,2'-bis[4,6-di(2-phenyl-2-propyl)phenol], rac-2,3-trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 73 publications
3
12
0
Order By: Relevance
“…and ). Control over molar mass dispersity of the poly( rac ‐lactides) is similar to the control given by recently reported bis(phenolate) complexes of scandium and yttrium complexes bearing a rigid 1,3‐dithiapropanediyl bridge in the backbone ( M w / M n = 1.05 for yttrium and M w / M n = 1.13 for scandium) . Figures show linear dependance of M n with the initial monomer:initiator ratio for the polymerization of rac ‐lactide initiated by 1 in CH 2 Cl 2 and THF and initated by 2 in CH 2 Cl 2 , consistent with controlled polymerization.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…and ). Control over molar mass dispersity of the poly( rac ‐lactides) is similar to the control given by recently reported bis(phenolate) complexes of scandium and yttrium complexes bearing a rigid 1,3‐dithiapropanediyl bridge in the backbone ( M w / M n = 1.05 for yttrium and M w / M n = 1.13 for scandium) . Figures show linear dependance of M n with the initial monomer:initiator ratio for the polymerization of rac ‐lactide initiated by 1 in CH 2 Cl 2 and THF and initated by 2 in CH 2 Cl 2 , consistent with controlled polymerization.…”
Section: Resultssupporting
confidence: 81%
“…Chiral initiator 3 gave heterotactic poly( rac ‐lactides) in THF ( P r = 0.77), showing that 3 is more stereoselective than initiators 1 and 2 . The tacticities of the polymers are similar to those for PLA prepared by [Sc(cyccp){N(SiMe 2 H) 2 }] ( P r = 0.74) and [Y(cyccp){N(SiMe 2 H) 2 }] ( P r = 0.68) . Ligand‐free indium initiators were found to be more active and more selective than indium bis(phenolate) precursors .…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…The polymerization proceeds in living fashion, although detailed initiation mechanism is not clear. Okuda reported that dithiobis(phenolate) scandium complexes such as 59 show high activity and selectivity for heterotactic polymerization of rac-lactide (P r up to 95%) (152)(153)(154). The coordination geometry of the tetradentate ligand ( or ) changes depending on the chirality of the ultimate repeating unit.…”
Section: Polymerization Of Lactidesmentioning
confidence: 99%
“…These polymerizations proceed via chain-end control mechanism. Recently, Okuda revealed Y, Sc, Ti, and Zr complexes with dithobis(phenolate) ligand such as 59 and 66 afford syndiotactic polymer from meso-lactide (154,165,166). Sc catalyst shows high syndioselectivity (P r = 0.92).…”
Section: Polymerization Of Lactidesmentioning
confidence: 99%